Transient oculomotor paralysis after cerebral angiography: A case report. Issue 22 (4th June 2021) - Qiu, Tao; Dai, Xiaoyan; Gong, Qingping; Pu, Rongmei; Xiao, Hua; Shi, Qiang; Deng, Xiaoyong; Chen, Ming; Guo, Zhaoyun
Abstract: Rationale: A special case of transient oculomotor nerve palsy after cerebral angiography. Patient concerns: A 55-year-old man developed oculomotor nerve dysfunction after right radial artery puncture angiography. Diagnoses: Cerebral angiography-induced oculomotor nerve palsy. Interventions: According to the patient's disease state, intravenous drip of dexamethasone 10 mg/d. Outcomes: Magnetic resonance imaging (MRI) showed no abnormalities, and the patient recovered completely after 48 hours of hormone therapy. Lessons: Transient eye palsy caused by contrast agent encephalopathy is a clinically rare neurological dysfunction caused by adverse effects of contrast agents. Early prevention and correct treatment are critical.